How do children with drug-resistant epilepsy sleep? A clinical and video-PSG study - Arhan, Ebru; Koç Uçar, Habibe; Aydın, Kürşad; Lüleci Hirfano?lu, Tu?ba; Serdaroğlu, Ayşe (Academic Press Inc Elsevier Science, 2021)
Aim: The aim of this study was to assess sleep architecture and sleep problems among three homogenous groups of children including children with drug-resistant focal epilepsy, children with newly diagnosed, drug-naive focal epilepsy, and healthy children using overnight video-polysomnography (V-PSG) and a sleep questionnaire.Methods: We compared sleep architecture among 44 children with drug-resistant focal epilepsy, 41 children with newly diagnosed, drug naive focal epilepsy, and 36 healthy children. All children underwent an overnight V-PSG recording, and their parents completed the Children's Sleep Habits Questionnaire (CSHQ). Sleep recordings were scored according to the American Academy of Sleep Medicine criteria.Results: Compared with children with newly diagnosed epilepsy and healthy controls, children with drug-resistant epilepsy receiving antiepileptic treatment showed disturbed sleep architecture, a significant reduction in time in bed, total sleep time, sleep efficiency, NREM3%, REM%, and a significant increase in awakenings, wake after sleep onset, and periodic leg movement. Children with drug-naive, newly diagnosed focal epilepsy showed a statistically significant increase in sleep onset latency, rapid eye movement (REM) latency, N1%, awakenings, and a significant decrease in time in bed when compared with the controls. Children with drug-resistant epilepsy had the highest CSHQ total scores, while children with drug-naive, newly diagnosed focal epilepsy had higher scores than healthy children.Conclusion: This is one of the few polysomnographic studies adding to the limited research on the sleep macrostructure of children with drug-resistant epilepsy compared with children with drug-naive, newly diagnosed focal epilepsy and healthy children by obtaining objective measurements of sleep concurrently with a validated questionnaire. Children with drug-resistant epilepsy had a greater incidence of sleep disturbance on the basis of qualitative aspects and architecture of sleep than children with newly diagnosed epilepsy, suggesting the need for referral of children with drug-resistant epilepsy for overnight sleep evaluation in order to improve the clinical management and optimize therapeutic strategies.
Keywords: Drug-Resistant Epilepsy; Sleep; Pediatric Polysomnography; Newly Diagnosed Epilepsy